Guidance on commodity risk assessment for the evaluation of high risk plants dossiers. (29th April 2019) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Di Serio, Francesco; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Fejer Justesen, Annemarie; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: Article 42 of the European Regulation (EU) 2016/2031, on the protective measures against pests of plants, introduces the concept of 'high risk plants, plant products and other objects' that are identified on the basis of a preliminary assessment to be followed by a commodity risk assessment. Following a request of the European Commission, this Guidance was developed to establish the methodology to be followed when performing a commodity risk assessment for high risk commodities (high risk plants, plant products and other objects). The commodity risk assessment performed by EFSA will be based on the information provided by the National Plant Protection Organisations of non‐EU countries requesting a lifting of import prohibition of a high risk commodity. Following international standards on pest risk analysis, this Guidance describes a two‐step approach for the assessment of pest risk associated with a specified commodity. In the first step, pests, associated with the commodity, that require risk mitigation measures are identified. In the second step, the overall efficacy of proposed risk reduction options for each pest is evaluated. A conclusion on the pest‐freedom status of the commodity is achieved. The method requires key uncertainties to be identified.